What doctors and nurses think about the residents' role within the Academic Hospital of Udine?. (13th November 2019) - Ruscio, E; Smaniotto, C; Del Pin, M; d'Angelo, M; Perri, G; Fabricci, M; Brunelli, L; Londero, C; Castriotta, L; Brusaferro, S
Abstract: Background: Residents have a significant role in both patient's care and daily ward activities; thus, they should be trained to adhere to hospital procedures and to guarantee best clinical practices and patient's safety. A survey was carried out to assess healthcare workers' (HCWs) opinions about residents' role and performance. Methods: Between February and March 2019, a paper-based/online survey was developed and distributed among both doctors (d) and nurses (n) in 17 (10 medical, 7 surgical) wards of Udine Academic Hospital, Italy. 22 Likert Scale questions (1-totally disagree, 5-totally agree) investigated 5 areas: respect of patient safety and privacy, healthcare quality, clinical risk management, role played within medical team, satisfaction concerning training activities planning. Profession, ward (medical/surgical), age and sex were considered as exposures. Descriptive analysis, median(M)±interquartile range, and ordered logistic regressions were performed with Stata software. Results: The survey involved 153/785 HCWs' (112/477 nurses and 41/308 doctors). All the units were represented with at least 1 HCWs; answers from both categories were collected in 82% of wards. Data analysis showed that nurses gave lower scores about residents' respect of patient privacy than doctors: patient privacy protection: M(d)=4±0, M(n)=4±1, OR(d/n) 2.60, [95%CI, 1.04-6.52]; sensitive data management: M(d)=4±0, M(n)=3±1, OR(d/n) 2.97, [95%CI, 1.26-7.02]. The same resulted regarding clinical risk management: patient record management: M(d)=4±0, M(n)=3±2, OR(d/n) 13.64 [95%CI 5.30-35.12]; proper hand hygiene: M(d)=4±1, M(n)=3±1, OR(d/n) 5.56 [95%CI 2.35-13.17]; incident reporting: M(d)=4±1, M(n)=3±2, OR(d/n) 7.05 [95%CI 3.14-15.86]. Conclusions: Nurses appeared to be more critical than doctors about residents performances in safety and privacy and clinical risk management areas. Reasons behind these different opinions should be investigated in order to improve constantly healthcare's quality. Key messages: Residents hold a key role in healthcare quality, therefore it is significant evaluate their practice regarding patient's safety and privacy. Doctors and nurses opinions on residents adherence to hospital procedures in order to guarantee best clinical practices and patient's safety differ significantly.